Education in movement spaces
1 online resource.
Keywords: "This book spotlights the distinct, intersecting, and coalitional possibilities of education in the spaces of ongoing movements for Native and Black liberation. Contributors highlight the importance of activist-oriented teaching and learning in temporary community encampments and other movement spaces for the preservation and expansion of resistance education. With chapters from scholars, educators, and organizers, this volume offers lessons taken from these experiences for nation-state schools, classrooms, and spaces of teacher learning that are most commonly experienced by Native and Black children and educators. Through attention to recent social movements across the United States-from Standing Rock to Black Lives Matter-this book demonstrates the vital connections between Indigenous and Black communities' educational futures"--